Development Rehabilitation Model for Female Drug Dependent - พงษ์พิทักษ์, ธนิกา; มีศิลป์, วัชรี; นิลบรรพ์, สำเนา; มณีอินทร์, ผกามาศ; ชัยพิชิตพันธ์, นันทา; บุญทับถม, นิภาวัล (Journal of The Royal Thai Army Nurses, 2019)
The research and development aim to study and develop a rehabilitation for female drug dependent. The FAST Model for women was investigated then the result was integrated with reviewing the related literature. The comparison between the new model of the rehabilitation for women and the FAST Model was conducted. The participants for the current research comprised of the female drug dependent and their relatives. Each was separated into two groups, an experimental group and control. The data were gathered by a questionnaire. The statistics applied for analyzing data combined with content analysis content analysis, descriptive statistics, paired t-test, independent t-test, Chi-square, Fisher extract and Man – Whitney test. An alpha of 0.05 was used as the cut-off for significance. The result found that the FAST model still had weak points needed to be considered. Those issues were resolved and applied as a ground theory for developing the new rehabilitation model. In the experiment revealed that the self-esteem, the intention of preventing in relapse, and the satisfaction on treatment activities of the experimental groups were significantly higher than controls at .05. After one month of the following up, the abstinent rate in the experimental group is higher than control at .05. The relatives of the female patients in the experimental group moreover showed a better attitude toward the patients. The relatives showed better satisfaction in the treatment activities compared with control at .05.